Hematologycal of Jambal siam (Pangasius hypophthalmus) That Using Aeromonas hydrophila Vaccine - Rika Sinaga; Morina Riauwaty; Henni Syawal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT The vaccine is alternative to controlling infection of Aeromonas hydrophila. The purpose of this research was to given understand the  hematology of (Pangasius hypophthalmus) that was with  Aeromonas hydrophila vaccine. This research was conducted  in April to June 2018. The method was an experimental method with a Completely Randomized Design (CRD) one factor with five treatments level and three times replication. The treatments were: Kn: The fishes that was not with given vaccine and   infected by Aeromonas hydrophila, Kp: The fishes that was not given vaccine and was infected by Aeromonas hydrophila, P1: Soaked with vaccine dose 1 ml/10 L water for 15 minutes, P2: Soaked with vaccine dose 1 ml/10 L water for 30 minutes, P3: Soaked with vaccine dose 1 ml/10 L water for 45 minutes. Pangasius hypophthalmus at average 8-10 cm of leght for 250 fishes. The challenge test was carried out for 22 days by Aeromonas hydrophila, the purpose of which was to determine imumunity of fish. The result shown that the total erythrocyte, hematocryte value, hemoglobin level, relative percent survival (RPS), antibody titer. The result swowed that immersion of the vaccine for 30 minutes could disease Motile Aeromonas Septicaemia. The results obtained from the research are, the  average of total erythrocyte is 245x104 cells/mm3, hematocryte value 28,00%, hemoglobin level 9,50 g/dl, relative percent survival (RPS) 83,33%, antibody titer 0,822%. Keywords : Hematology, Pangasius hypophthalmus, HydroVac vaccine, Aeromonas hydrophila, erythrocyte.